Behavioral Deficits Following Withdrawal from Chronic Ethanol Are Influenced by SLO Channel Function in Caenorhabditis elegans. Issue 3 (1st July 2017) - Scott, Luisa L; Davis, Scott J; Yen, Rachel C; Ordemann, Greg J; Nordquist, Sarah K; Bannai, Deepthi; Pierce, Jonathan T
Abstract: Symptoms of withdrawal from chronic alcohol use are a driving force for relapse in alcohol dependence. Thus, uncovering molecular targets to lessen their severity is key to breaking the cycle of dependence. Using the nematode Caenorhabditis elegans, we tested whether one highly conserved ethanol target, the large-conductance, calcium-activated potassium channel (known as the BK channel or Slo1), modulates ethanol withdrawal. Consistent with a previous report, we found that C. elegans displays withdrawal-related behavioral impairments after cessation of chronic ethanol exposure. We found that the degree of impairment is exacerbated in worms lacking the worm BK channel, SLO-1, and is reduced by selective rescue of this channel in the nervous system. Enhanced SLO-1 function, via gain-of-function mutation or overexpression, also dramatically reduced behavioral impairment during withdrawal. Consistent with these results, we found that chronic ethanol exposure decreased SLO-1 expression in a subset of neurons. In addition, we found that the function of a distinct, conserved Slo family channel, SLO-2, showed an inverse relationship to withdrawal behavior, and this influence depended on SLO-1 function. Together, our findings show that modulation of either Slo family ion channel bidirectionally regulates withdrawal behaviors in worm, supporting further exploration of the Slo family as targets for normalizing behaviors during alcohol withdrawal.